The Relationship Between Crystalloid Fluid Administration and Electrolyte Balance in Critically Ill Patients : A Comprehensive Systematic Review - Bery Andara; Dianalia Nurarifany (International Medical Journal Corp. Ltd, 2026)
Introduction: The choice between balanced crystalloids and 0.9% normal saline for fluid resuscitation in critically ill patients remains debated. While saline is widely used, concerns exist regarding its electrolyte and acid-base effects. Methods: This systematic review synthesized data from 80 studies (RCTs, etc) examining crystalloid administration in critically ill adults. Outcomes focused on significant positive biochemical and clinical effects of balanced crystalloids over saline. Results: Balanced crystalloids demonstrated consistently significant positive effects on electrolyte balance. Serum chloride was significantly lower with balanced solutions versus saline: mean difference −7 mEq/L in trauma (p<0.05) [30], −5.68 mEq/L in sepsis (p=0.001) [1], and −4.3 mmol/L in pancreatitis (p<0.001) [7]. Base excess and bicarbonate were significantly improved in TBI patients receiving balanced fluids (BE −1.35 vs. −3.20, p=0.049) [3]. In DKA, balanced crystalloids significantly reduced time to resolution by 3.51–5.36 hours [21,22] and lowered post-resuscitation chloride (MD −4.26 mmol/L) [22]. In acute pancreatitis, balanced solutions significantly reduced SIRS (17.0% vs. 29.3%, p=0.024) and increased organ failure-free days [7]. Hyperchloremia at 48 hours independently predicted 30-day mortality in trauma (p<0.001) [14]. However, large RCTs found no significant mortality difference in unselected critically ill adults [9,10,13]. Discussion: The consistent chloride-raising effect of saline is mechanistically explained by Stewart’s strong ion theory. Significant benefits of balanced crystalloids emerge in high-volume contexts (DKA, pancreatitis, trauma), but are diluted in heterogeneous ICU populations. Conclusion: Balanced crystalloids produce significantly superior electrolyte profiles and are recommended as default resuscitation fluids, particularly in DKA, pancreatitis, and traumatic brain injury.